The links between e-logistics service quality, attitude and repurchase intention of Gen Z in e-commerce - Thao Phuong Vu; Duong Tuan Nguyen (Journal of Trade Science)
Purpose – This study aims to identify the dimensions that represent e-logistics service quality (e-LSQ) in e-commerce from the perspective of Generation Z customers in Vietnam. Additionally, it seeks to evaluate the impact of these dimensions on repurchase intention, including their indirect effects through the mediating variable of attitude. Design/methodology/approach – The study applied in-depth interviews and focus group discussions as methods for developing measurement scales and the research model. Quantitative analyses are conducted using a dataset gathered from 290 Gen Z customers in Vietnam. Partial least squares structural equation modeling (PLS-SEM) is employed to test the measurement model and validate the research hypotheses. Findings – The results revealed that all four dimensions of e-LSQ – return, condition, timeliness and availability – significantly impact repurchase intention. Additionally, besides the direct impact on repurchase intention, the study found the mediating role of attitude in the relationships between availability, condition and return and the repurchase intention of Gen Z customers. Practical implications – This study provides empirical evidence that enables enterprises to identify the critical determinants of e-LSQ in fostering the repurchase intention of Generation Z customers. Based on the findings, e-commerce businesses can formulate strategies to effectively enhance the repurchase intention of Generation Z customers through improvements in e-LSQ. Originality/value – This study contributes to diversifying the body of knowledge on the topic of e-LSQ and significantly enhances the understanding of Gen Z customers’ consumption behaviors in the context of e-commerce. Notably, the findings elucidate the mechanism through which e-LSQ influences repurchase intention through attitude. These results hold value both academically, by offering insights for researchers, and practically, by providing e-commerce managers with a deeper understanding of the pivotal role of e-LSQ in business operations.